High resolution, label-free photoacoustic imaging of live chicken embryo developing in bioengineered eggshell - Sharma, Arunima (2021)
Chicken embryos have been proven to be an attractive vertebrate model for biomedical research. They have helped in making significant contributions for advancements in various fields like developmental biology, cancer research and cardiovascular studies. However, a non-invasive, label-free method of imaging live chicken embryo at high resolution still needs to be developed and optimized. In this work, we have shown the potential of photoacoustic tomography (PAT) for imaging live chicken embryos cultured in bioengineered eggshells. Laser pulses at wavelengths of 532 and 740 nm were used for attaining cross-sectional images of chicken embryos at different developmental stages. Cross-sections along different depths were imaged to gain knowledge of the relative depth of different vessels and organs. Due to high optical absorption of vasculature and embryonic eye, images with good optical contrast could be acquired using this method. We have thus reported a label-free method of performing cross-sectional imaging of chicken embryos at high resolution demonstrating the capacity of PAT as a promising tool for avian embryo imaging.